LVO (Learning Virtual Objects) implementation as a methodological strategy for teaching English language - León León, Jairo (Rastros Rostros, 2011)
Research “Implementation of vlo as a methodological strategy for teaching the English language” of Universidad Cooperativa de Colombia, Bucaramanga, 2010, is being developed at the College Aurelio Martinez Mutis for grade VI of primary education. This research is developing guidelines for aquasi-experimental design, which will take two groups, one control and one experimental, in the latter policy be implemented and supported by theoretical investigations regarding the Mozart effect and the use of music in teaching the English language. In the magazine No. 26 appear the results of the research process.